1997
DOI: 10.2307/3870559
|View full text |Cite|
|
Sign up to set email alerts
|

Antisense Suppression of 4-Coumarate:Coenzyme A Ligase Activity in Arabidopsis Leads to Altered Lignin Subunit Composition

Abstract: The phenylpropanoid enzyme 4-coumarate:coenzyme A ligase (4CL) is considered necessary to activate the hydroxycinnamic acids for the biosynthesis of the coniferyl and sinapyl alcohols subsequently polymerized into lignin. To clarify the role played by 4CL in the biosynthesis of the guaiacyl (G) and syringyl (S) units characteristic of angiosperm lignin, we generated 4CL antisense Arabidopsis lines having as low as 8% residual 4CL activity. The plants had decreases in thioglycolic acid-extractable lignin correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 0 publications
3
73
0
1
Order By: Relevance
“…However, the transgenic plants displayed abnormal plant growth and development (Elkind et al, 1990;Piquemal et al, 1998;Tamagnone et al, 1998), indicating that Phe ammonia-lyase, cinnamoyl-coenzyme A reductase, and Myb proteins are not ideal targets for genetic manipulation of lignin in forages and trees. In contrast, transgenic plants with repression of genes such as 4-coumarate:coenzyme A ligase (Kajita et al, 1996;Lee et al, 1998;Hu et al, 1999) and CCoAOMT showed normal growth patterns, suggesting that these genes are ideal targets for genetic manipulation of lignin in forages and trees.…”
Section: Ccoaomt Is An Ideal Target For Genetic Manipulation Of Lignimentioning
confidence: 95%
“…However, the transgenic plants displayed abnormal plant growth and development (Elkind et al, 1990;Piquemal et al, 1998;Tamagnone et al, 1998), indicating that Phe ammonia-lyase, cinnamoyl-coenzyme A reductase, and Myb proteins are not ideal targets for genetic manipulation of lignin in forages and trees. In contrast, transgenic plants with repression of genes such as 4-coumarate:coenzyme A ligase (Kajita et al, 1996;Lee et al, 1998;Hu et al, 1999) and CCoAOMT showed normal growth patterns, suggesting that these genes are ideal targets for genetic manipulation of lignin in forages and trees.…”
Section: Ccoaomt Is An Ideal Target For Genetic Manipulation Of Lignimentioning
confidence: 95%
“…Moreover, the combination of distinct substrate preferences with differences in gene-promoter and protein fine structure may facilitate not only a large diversity of genetically programmed metabolic functions of the individual isoenzymes, including pathway-specific associations with biosynthetically related enzymes in metabolite channeling (37-39), but also regular or potential functional overlaps or mutual replacements upon malfunction or down-regulation, as has been investigated so far only for the class I isoforms (4,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that TK has a remarkably high flux control coefficient (Ͼ0.7) for phenylpropanoid metabolism. This is similar to or larger than the effects of the decreased expression of phenylalanine ammonia-lyase (Bate et al, 1994;Howles et al, 1996;Sewalt et al, 1997), 4-coumarate:CoA lyase (Lee et al, 1997), and cinnamate-4-hydroxylase (Sewalt et al, 1997), three enzymes that build a regulatory unit that responds to a range of developmental and environmental factors (Chapple and Carpita, 1998;Koopman et al, 1999).…”
Section: A Small Decrease In Tk Expression Leads To Lower Levels Of Amentioning
confidence: 98%